Effectiveness of the autumn 2023 COVID-19 vaccine dose in hospital-based healthcare workers: results of the VEBIS healthcare worker vaccine effectiveness cohort study, seven European countries, season 2023/24 - Savulescu, Camelia (2024)
COVID-19 vaccination recommendations prioritise healthcare workers (HCWs), considering their exposure to severe acute respiratory coronavirus 2 (SARS-CoV-2) and their key role in the functioning of healthcare systems. In the European Union/European Economic Area (EU/EEA), HCWs were considered a priority for COVID-19 revaccination during the autumn 2023 campaign [1], and the World Health Organization (WHO) recommended revaccination of HCWs 12 months after their last dose [2]. Because the Omicron sub-lineage XBB.1.5 predominated in spring 2023, the COVID-19 vaccines were adapted to target this emerging strain, and the first XBB.1.5 vaccine was authorised for use in the EU/EEA in August 2023. Omicron BA.2.86/JN.1 emerged in the EU/EEA at the end of 2023, according to data available on the European Respiratory Virus Surveillance Summary (ERVISS) [3]. Evidence for COVID-19 vaccine recommendation in the HCW population remains scarce. Within the Vaccine Effectiveness, Burden and Impact (VEBIS) project, we aimed to measure the COVID-19 vaccine effectiveness (CVE) in HCWs, in the winter season 2023/24.